JBRMR 2018
DOI: 10.24052/jbrmr/v12is02/mpocsrdin
|View full text |Cite
|
Sign up to set email alerts
|

Managerial perceptions of corporate sustainability reporting determinants in Nigeria

Abstract: This study investigated managerial perceptions of the determinants of sustainability reporting in Nigeria. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 13 publications
1
37
1
Order By: Relevance
“…In China, Zhao and Patten (2016) indicate that managers perceive the interplay of a variety of coercive, normative and mimetic pressures as influences on social and environmental disclosures. Nwobu et al (2018) report that, in Nigeria, initiation by the chief executive officer, investors' concern with long-term performance of the business, corporate governance code, employee training, Central Bank of…”
Section: Managerial Perceptionsmentioning
confidence: 99%
See 3 more Smart Citations
“…In China, Zhao and Patten (2016) indicate that managers perceive the interplay of a variety of coercive, normative and mimetic pressures as influences on social and environmental disclosures. Nwobu et al (2018) report that, in Nigeria, initiation by the chief executive officer, investors' concern with long-term performance of the business, corporate governance code, employee training, Central Bank of…”
Section: Managerial Perceptionsmentioning
confidence: 99%
“…This is based on the assumption that training plays a crucial role in enhancing two of the primary sources of competitive advantage for a firm: its human capital and its organisational knowledge (Subramaniam and Youndt, 2005;Lopez-Cabrales et al, 2006). In Nigeria, Nwobu et al (2018) report that, among other factors, employee training motivates the adoption of SR. Therefore, we argue that companies whose employees do not receive training are less likely to adopt SR, leading to our second hypothesis: transparency, accountability and credibility, reduced legal risks and costs, and more ethical behaviour within the company and throughout its value chain.…”
Section: Expertisementioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between foreign presence of a company and CSRR suggests that as companies expand their operations to foreign environments, there is tendency for them to incorporate developments that have been institutionalized in those environments (Nwobu, 2017). Beddewela & Herzig (2013) found that Sri Lankan subsidiaries' of multinationals disclosure behaviour (i.e.…”
Section: Literature Reviewmentioning
confidence: 99%